Hubungan Tingkat Pengetahuan Dan Status Ekonomi Dengan Minat Menggunakan Gigi Tiruan Sebagian Lepasan (Jurnal Terapi Gigi dan Mulut, 2022)
According to the 2018 Basic Health Research (Ministry of Health of the Republic of Indonesia, 2018) the population with dental and oral health problems in West Java is 58.0%, and 11.9% receiving treatment from dental medical personnel. The proportion of actions in overcoming dental and oral problems in the province of West Java for the installation of dentures is 4.9%, and the installation of implant dentures is 0.1%. This study aims to prove the relationship between knowledge level and economic status with interest in using removable partial dentures. The type of research used is an analytic survey with a cross sectional design. The sample is 93 pre-elderly respondents who have lost at least 1 tooth. The average pre-elderly in Cipeundeuy Village has high knowledge (43.0%), high economic status (65.6%), and has a moderate interest in using removable partial dentures (46.2%). Data analysis used Chi-Square statistical test and the results showed that knowledge with interest in using removable partial dentures had a significance of 0.006 while the relationship between economic status and interest in using removable partial dentures had a significance of 0.024. This shows that the p value <0.05 means Ho is rejected and Ha is accepted, so that the level of knowledge and economic status has a significant relationship with the interest in using removable partial dentures of pre-elderly Cipeundeuy Village. Keywords : Level Of Knowledge About Dentures, Economic Status, Interest In Using Dentures